(untitled) (TEL Tempo, Espaço e Linguagem, 2022)
This article aims, once the original link between Marxism and science fiction has been established, to explore the contemporary context accoding to the possibilities offered through the works of this literary subgenre, with emphasis on its dystopian variant. We identified this dystopian impulse as a symptom of what the British thinker Mark Fisher called “reflective impotence” and, based on this observation, we seek to establish some possible reflections on this particular intersection between literature and society.